Comparative anatomy of leaf petioles in temperate trees and shrubs: the role of plant size, environment and phylogeny. (7th February 2022) - Filartiga, Arinawa Liz; Klimeš, Adam; Altman, Jan; Nobis, Michael Peter; Crivellaro, Alan; Schweingruber, Fritz; Doležal, Jiří
Abstract: Background and Aims: Petioles are important plant organs connecting stems with leaf blades and affecting light-harvesting ability of the leaf as well as transport of water, nutrients and biochemical signals. Despite the high diversity in petiole size, shape and anatomy, little information is available regarding their structural adaptations across evolutionary lineages and environmental conditions. To fill this knowledge gap, we investigated the variation of petiole morphology and anatomy of mainly European woody species to better understand the drivers of internal and external constraints in an evolutionary context. Methods: We studied how petiole anatomical features differed according to whole-plant size, leaf traits, thermal and hydrological conditions, and taxonomic origin in 95 shrubs and trees using phylogenetic distance-based generalized least squares models. Key Results: Two major axes of variation were related to leaf area and plant size. Larger and softer leaves are found in taller trees of more productive habitats. Their petioles are longer, with a circular outline and are anatomically characterized by the predominance of sclerenchyma, larger vessels, interfascicular areas with fibres and indistinct phloem rays. In contrast, smaller and tougher leaves are found in shorter trees and shrubs of colder or drier habitats. Their petioles have a terete outline, phloem composed of small cells and radially arranged vessels, fibreless xylem and lamellar collenchyma. Individual anatomical traits were linked to different internal and external drivers. Petiole length and vessel diameter increase with increasing leaf blade area. Collenchyma becomes absent with increasing temperature, and petiole outline becomes polygonal with increasing precipitation. Conclusions: We conclude that species' temperature and precipitation optima, plant height, and leaf area and thickness exerted a significant control on petiole anatomical and morphological structures not confounded by phylogenetic inertia. Species with different evolutionary histories but similar thermal and hydrological requirements have converged to similar petiole anatomical structures.